2023
DOI: 10.1590/1517-8692202329012022_0323
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Movement Characteristics in Volleyball Athletes

Abstract: Introduction Passing and serving are the most direct and efficient tactics for scoring points in volleyball. The recoil of the upper limbs in dominating the ball requires strength and muscular explosion, where the effect of the body's angular momentum accompanies a joint and rhythmic action. Objective This study aims to analyze muscle strength in upper limb movements in volleyball athletes. Methods Several volleyball players volunteered for the research. The movement when the athlete hits the ball was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Therefore, this study provides evidence of a substantial link between explosive power, elbow angle, jump height, and smash accuracy in volleyball. Previous studies [20][21][22] have also reported similar results, further emphasizing the noteworthy relationship between these variables and smash accuracy.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, this study provides evidence of a substantial link between explosive power, elbow angle, jump height, and smash accuracy in volleyball. Previous studies [20][21][22] have also reported similar results, further emphasizing the noteworthy relationship between these variables and smash accuracy.…”
Section: Discussionsupporting
confidence: 76%